The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41586-020-03154-y
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-based mechanism for transient forgetting

Abstract: Active forgetting is an essential component of the brain’s memory management system 1 . Forgetting can be permanent, in which prior memory is lost completely; or transient, in which memory exists in a temporary state of impaired retrieval. Such temporary blocks on memory seem universal, and can disrupt an individual’s plans, social interactions, and ability to make rapid, flexible and appropriate choices. However, the neurobiological mechanisms that cause transient forgetting are unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…A large number of studies reported a wide range of olfactory learning‒related changes in synaptic plasticity in the Drosophila MB (Akalal et al, 2010; Berry et al, 2018; Bilz et al, 2020; Boto et al, 2014; Boto et al, 2019; Bouzaiane et al, 2015; Cohn et al, 2015; Dylla et al, 2017; Felsenberg et al, 2017; Felsenberg et al, 2018; Gervasi et al, 2010; Handler et al, 2019; Hige et al, 2015; Louis et al, 2018; McCurdy et al, 2021; Owald et al, 2015; Perisse et al, 2016; Placais et al, 2013; Sabandal et al, 2021; Sejourne et al, 2011; Stahl et al, 2021; Wang et al, 2008; Yu et al, 2006; Yu et al, 2005; Zhang and Roman, 2013; Zhang et al, 2019b; Zhou et al, 2019). However, some studies differed with respect to the location (i.e., the specific MB compartment), direction (i.e., potentiation vs. depression) and whether the change occurs in presynaptic KCs or postsynaptic MBONs.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies reported a wide range of olfactory learning‒related changes in synaptic plasticity in the Drosophila MB (Akalal et al, 2010; Berry et al, 2018; Bilz et al, 2020; Boto et al, 2014; Boto et al, 2019; Bouzaiane et al, 2015; Cohn et al, 2015; Dylla et al, 2017; Felsenberg et al, 2017; Felsenberg et al, 2018; Gervasi et al, 2010; Handler et al, 2019; Hige et al, 2015; Louis et al, 2018; McCurdy et al, 2021; Owald et al, 2015; Perisse et al, 2016; Placais et al, 2013; Sabandal et al, 2021; Sejourne et al, 2011; Stahl et al, 2021; Wang et al, 2008; Yu et al, 2006; Yu et al, 2005; Zhang and Roman, 2013; Zhang et al, 2019b; Zhou et al, 2019). However, some studies differed with respect to the location (i.e., the specific MB compartment), direction (i.e., potentiation vs. depression) and whether the change occurs in presynaptic KCs or postsynaptic MBONs.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous signals relayed by upstream elements (i.e., recurrent loops or pacemaker neurons) may induce spontaneous DAN activity in the absence of identified environmental stimuli, providing homeostatic regulation of the memory circuit (Scaplen et al, 2021;Vaccaro et al, 2017). Alternatively, persistent PPL1 DAN activity may reflect spurious exogenous sensory input (i.e., unrelated to planned experiments), causing either proactive or retroactive interference (in a cognitive psychology context) that contributes to the erosion of memory (Postman and Underwood, 1973;Berry et al, 2015;Sabandal et al, 2021). As such, our observation…”
Section: Persistent Dan Activity In Ltm Formationmentioning
confidence: 99%
“…On the behavioral front, research over the past several decades has transformed the fruit fly into a key model organism for the study of associative learning and choice behavior [33][34][35] . A rich body of experiments has shown that flies can learn a variety of Pavlovian conditioning paradigms [36][37][38][39][40][41][42] and exhibit features common in vertebrate memory, such as forgetting, re-evaluation, and consolidation, amongst others [43][44][45][46][47][48][49][50] . However, most existing tasks rely on studying the place preference behavior of groups of flies.…”
Section: Introductionmentioning
confidence: 99%